Migration bet and marital game.Impacts of departure on the matrimonial paths of sub-Saharan African women in France (Villeurbanne) - (:unkn) unknown (My University, 2022)
Standing at the crossroads of the sociology of migration, family and gender, this thesis investigates the effects of the migratory experience on the marital paths of women who have left West and Central African countries as adults and settled in France for a long time. Beyond the question of gains/losses due to migration for these women, it aims to identify the forms and modalities of the (re)arrangements made within the private sphere, both in terms of the relationship to norms and of concrete practices. Adopting a life-course approach, the study is mainly based on biographical interviews and focus groups conducted with migrant women, in a fieldwork based in Villeurbanne.This research reveals gender identities as a place that crystallises the issues and tensions induced by the migratory situation. Since the gender roles inherited from the societies of origin do not find the conditions for their reproduction in France, they are being re-examined. This calls into question the statuses of the partners – specifically by endangering male authority – in a migratory context that challenges the very definition of the couple, at a distance from kinship networks.Beyond the diversity of marital and migratory situations on arrival in France, the survey points out that the migratory experience is as a strong element in the formation of matrimonial destinies, but it is not sufficient to account for their variations. Marital expectations are indeed shaped by parameters such as age, educational capital and social origin, (gendered) family socialisation or marital heritage - and not least, the disappointments that constitute it. However, by distancing women from their social and family environment as well as providing them with support of legitimation (institutional, normative, symbolic) for the exercise of individual marital choices, migration to France facilitates the expression and realisation of the latter, particularly in their more egalitarian aspirations.In
Keywords: African Research